Innovative inner sleeve composite bolted connections for modular steel constructions: Experimental and numerical studies. (1st April 2023) - Shi, Feng-Wei; Li, Yu-Ming
Abstract: The application scenarios of modular steel constructions (MSCs) are becoming more and more extensive due to their exceptional advantages: minimum on-site work, and higher construction speed and quality. Inter-module connections are the critical components, which can significantly affect the integrity and seismic behavior of MSCs. This study proposed an innovative inner sleeve composite bolted connection which combines blind bolts, high-strength bolts and inner sleeve to improve the constructability and seismic behavior. Experimental tests on four full-scale cruciform connections composed of hollow structural steel (HSS) columns and H-section steel beams with different configurations were carried out under cyclic load. The failure modes, moment-rotation relations, initial rotational stiffness, ductility and energy dissipation were analyzed. GB 50011–2010 was used to evaluate the seismic performance and verify the applicability for the seismic design of the proposed connection, in which the lower limit of elastic inter-story drift ratio [ θ e ] is 0.004 rad (or 1/250) and that of elasto-plastic inter-story drift ratio [ θ p ] is 0.02 rad (or 1/50). The yield inter-story drift ratio, [ θ y ] = 4.00–6.75[ θ e ], and the ultimate inter-story drift ratio, [ θ u ] = 1.00–2.00[ θ p ] for the test specimens under cycle load, demonstrating the satisfactory deformation capacity and ductility. Furthermore, EC3 Part 1–8 was adopted to evaluate the stiffness characteristic of the proposed connection, indicating that the proposed connection can be classified as a "semi-rigid" and partial strength connection. Finally, refined numerical models calibrated against the experimental results were established and parametric evaluation was conducted based on the numerical models. The results demonstrate that the effect of the thickness of the inner sleeve and column in the panel zone and the diameter of the blind bolt and vertical high-strength bolt is insignificant. The presented research will provide useful references for further application and popularization of MSCs. Highlights: An innovative inter-module connection for modular steel construction was proposed. Four cruciform full-scale specimens were tested under cyclic load. Load-transferring mechanism and seismic performance were investigated. Numerical analysis was conducted for further discussion of the mechanical performance of the proposed connection.